Effect of acid treatment substrate for supercapacitor electrode based on multi-walled carbon nanotubes - Paweena Dulyaseree; Winadda Wongwiriyapan (My University, 2021)
Abstract Effect of acid treatment substrate for supercapacitor based on multi-walled carbon nanotubes (MWNTs) electrode was investigated. The electrode was used as stainless steel type 304 (SS304) and was with hydrochloric acid (HCl) acid-treated before use. Firstly, SS304 substrates were soaked in 37% HCl for designated time. Acid treatment times were varied at 0, 5, 10 and 15 min. Their surface morphology, elemental components and hydrophilicity property of the acid-treated SS304 were analyzed. The 10-min-treated SS304 show the lowest contact angles, indicating the best hydrophilicity property. Electrode material was prepared by composites of MWNTs, polyvinylidene fluoride (PVDF) and n-methyl-2-pyrrolidone (NMP) with an area of 5x5 mm 2 . Their cyclic voltammetry (CV), galvanostatic charge/discharge (CD) and electrochemical impedance spectroscopy (EIS) were characterized. The 10-min-treated SS304 exhibits the best performance with a specific capacitance (SC) of 261.04 Fg −1 . The improvement of the SC of the acid-treated substrate was contributed to the adhesion improvement between a current collector and an electrode material, and the hydrophilicity improvement, resulting in a large amount of electrolyte ions accessing into the electrode materials and subsequently enhancement of their capacitive characteristics.
Keywords: Polyvinylidene fluoride; Supercapacitor Materials and Fabrication